KENDALA DALAM PEMBELAJARAN BAHASA ARAB DI MI MUHAMMADIYAH PLUS LEKSONO - Rachma, Lupita; Sujarwo; Savira, Nia (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
In the process of learning Arabic, teachers and students often face various kinds of obstacles. This article aims to know and understand the Arabic learning process, identify obstacles during the Arabic learning process, and find solutions to overcome these obstacles. This is done in order to help the government, teachers, and students improve the quality of Arabic language learning in MI/SD. This research is a research that uses qualitative approach methods. With data collection techniques using interviews, observation, and documentation techniques directly in the field. When the author conducted research at MI Muhammadiyah Plus Leksono, the author found several obstacles in learning Arabic there, such as teacher obstacles in choosing the right learning strategy for students, students less focused on following Arabic learning, students in lower grades still have difficulty reading and writing in Arabic, lack of student learning motivation during the Arabic learning process, and students' lack of interest in learning Arabic. These obstacles can be used as joint evaluation materials so that Arabic language learning in MI/SD can be more qualified